Factors Associated with Scabies in The Community in The Area of The Lubuk Begalung Public Health Center - Riyana Husna; Tri Joko; N Nurjazuli (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Scabies was still a public health problem in Indonesia. Scabies was found in places with an unhealthy environment and poor personal hygiene. The purpose of this study was to determine the relationship between risk factors and the incidence of scabies at the Lubuk Begalung Health Center. This research was observational explanatory with a cross-sectional study design approach. The primary data source used a questionnaire containing data on respondent characteristics, personal hygiene and the environment, while secondary data obtained from the puskesmas and the Padang city health office was scabies disease data in 2020. The sample in this study amounted to 112 people using random sampling. The results of the research data were analyzed using the Chi-Square test and multiple logistic regression (multiple regression). The research sample was dominated by males (55.4%) and female (44.6%) and high school students. and above (SMA) (33.0%). The data also showed that 34.8% of respondents suffered from scabies. The results showed that there was a relationship between gender (p=0.026) clothing cleanliness (0.000) skin hygiene (0.065) clean water (0.006) occupancy density (0.010) ventilation area (0.002) and the incidence of scabies. While the variables of hand and nail hygiene (0.593) towel cleanliness (0.986) cleanliness of bed linen (0.142) humidity (0.055) was not associated with the incidence of scabies. This study concludes that the variables that affect the incidence of scabies are cleanliness of clothes, cleanliness of bed linen and bed linen, occupancy density, ventilation area with p less than 0.05. It was hoped that the community will improve personal and environmental hygiene and increase awareness of scabies disease so that it can prevent scabies from spreading to other families.Skabies masih menjadi masalah kesehatan masyarakat Indonesia. Kudis ditemukan di tempat-tempat dengan lingkungan yang tidak sehat dan kebersihan pribadi yang buruk. Tujuan penelitian ini adalah untuk mengetahui hubungan faktor risiko dengan kejadian skabies di Puskesmas Lubuk Begalung. Jenis penelitian ini adalah observasional explanatory dengan pendekatan desain studi cross sectional. Sumber data primer menggunakan kuesioner yang berisi data karakteristik responden, personal hygiene dan lingkungan, sedangkan data sekunder yang diperoleh dari puskesmas dan dinas kesehatan kota Padang adalah data penyakit scabies tahun 2020. Sampel dalam penelitian ini berjumlah 112 orang dengan menggunakan random contoh. Data hasil penelitian dianalisis menggunakan uji Chi Square dan regresi logistik berganda (multiple regression). Sampel penelitian didominasi oleh siswa laki-laki (55,4%) dan perempuan (44,6%) dan SMA. ke atas (SMA) (33,0%). Data tersebut juga menunjukkan bahwa 34,8% responden menderita skabies. Hasil penelitian menunjukkan bahwa ada hubungan antara jenis kelamin (p=0,026) kebersihan pakaian (0,000) kebersihan kulit (0,065) air bersih (0,006) kepadatan hunian (0,010) luas ventilasi (0,002) dengan kejadian skabies. Sedangkan variabel kebersihan tangan dan kuku (0,593) kebersihan handuk (0,986) kebersihan sprei (0,142) kelembaban (0,055) tidak berhubungan dengan kejadian skabies. Penelitian ini menyimpulkan bahwa variabel yang mempengaruhi kejadian skabies adalah kebersihan pakaian, kebersihan sprei dan sprei, kepadatan hunian, luas ventilasi dengan p kurang dari 0,05. Diharapkan kepada masyarakat untuk meningkatkan kebersihan diri dan lingkungan serta meningkatkan kewaspadaan terhadap penyakit skabies sehingga dapat mencegah penyebaran penyakit skabies ke keluarga lain.